140 GROUP G STREPTOCOCCUS: AN UNUSUAL CAUSE OF ENDOCARDITIS IN AN HIV PATIENT. Issue 1 (1st January 2007) - Babar, F.; Sarwar, S.; Ismail, M. K.
Abstract : Introduction: Group G streptococci have only occasionally been implicated as a cause of native valve endocarditis. This case report describes a group G streptococcal endocarditis in a drug-resistant HIV patient with severe valvular dysfunction. Case Report: A 47-year-old African American male with a past medical history of HIV and CD4 count 10 presented with a 1-week history of fever and left wrist pain. He was not on antiretroviral therapy due to drug-resistant HIV. On examination, temperature was 104°F, BP 115/74, pulse 107, with RR 22/min. He had left wrist tenderness without erythema and swelling. Heart auscultation was unremarkable for any murmur. Laboratory studies revealed leukocyte count of 3, 500/μL with 66% bands, creatinine 5.7 mg/dL, and BUN 54 mg/dL. Chest radiography was unremarkable. Urinalysis showed 2+ proteins but no blood. Blood culture grew penicillin-sensitive group G Streptococcus, and the patient was started on parental penicillin G (PCN-G) for cellulitis. On the third day of admission, he developed shortness of breath with hypoxemia. Cardiac auscultation revealed an early diastolic murmur. Chest radiography revealed bilateral pulmonary infiltrates with normal heart size. An echocardiogram showed severe aortic regurgitation with multiple aortic valve vegetations. A diagnosis of infective endocarditis with congestive heart failure was made. He was treated medically with Lasix, along with nitrates. Surgical aortic valve replacement was not an early consideration due to his severely compromised immune status. Over the course of therapy, his hypoxemia resolved and creatinine improved to 3.3 mg/dL. For his HIV therapy, Fuzeon, a fusion protein inhibitor, and HAART were started for resistant HIV genotype and latter discharged with an 8-week intravenous PCN-G home infusion therapy. Surveillance cultures remained negative, and he is currently awaiting aortic valve replacement. Discussion: Group G streptococci are gram-positive cocci, which are usually beta-hemolytic. Group G infections are rare but are serious when they occur in settings of underlying predisposing conditions, including diabetes mellitus, alcoholism, immunosuppression, and malignancy. In a series of studies, the most common source of group G bacteremia was found to be cellulitis. In this patient, cellulitis was presumed to be the source of bacteremia. Group G streptococcal endocarditis has a characteristic aggressive course as shown by severe aortic valve dysfunction and acute pulmonary edema in this case. Impaired immunity due to advanced AIDS likely contributed to this aggressive course. Mortality is usually high if it is not recognized early.